Eco-effective Sustainable Risk Assessment Model for homogeneous solid waste mortars based on the Cradle to Cradle paradigm - Cadenas, Nigme; Vásquez Stanescu, Carmen Luisa; Gómez-Caicedo, Melva Inés; Gaitan-Angulo, Mercedes; Briñez Torres, Carlos Yesid (Frontiers in Sustainability, 2023)
Introduction The unrestricted use of non-renewable natural resources in masonry mortars and the rapid increase in solid waste contribute to the deterioration of the environment. It is a priority for the United Nations to promote growth without compromising the ability of new generations to attend to their own; for this purpose, 17 Sustainable Development Goals for all countries have been formulated. The present work arises from the need to propose a model to evaluate, in the design phase, homogeneous solid waste and total or partial substitutes for some of the components of the mortars used in the construction sector, based on the Cradle to Cradle paradigm, which has the objective of including improved materials for the health of living beings and the environment by establishing a circular system in the manufacture of mortars including only safe and healthy materials that can be reused with a guarantee of not affecting the health of living beings and the environment and contributing to sustainability. Methods Based on the positivist epistemological current, projective documentary research begins by analyzing scientific publications that recommend the use of solid waste only to verify its rheological properties, ignoring how the inclusion of this material can affect living beings and the environment; it is contrasted with the results of published public access research regarding the chemical substances that make up said material. Results The eco-effective model is designed and its application is validated in identifying potential risks to the health of living beings and the environment in the waste of the selected cases; recommending the avoidance of recycling those materials that cause concern; contributing improved mortar designs for living beings and the planet, which minimize the use of natural resources and increase productivity in the field of construction; and implementing this vision through continuous development and improvement. Conclusions The eco-effective model facilitates doing the right things from the design stage, promoting growth with opportunities, diversity, and abundance for the present generation as well as future generations.